Issues in multiagent resource allocation - Chevaleyre, Yann (Informatica (Ljubljana), 2006)
The allocation of resources within a system of automomous agents, that not only have preferences over alternative allocations of resources but also actively participate in computing an allocation, is an exciting area of research at the interafe of computer science and ecomomics. This paper is a survey of some of the most salient issues in multiagent resource allocation. In particular, we review various languages to represent the preferences of agents over altrnative allocations of resources as well as different measures of social welfare to assess the overall quality of an allocation. WE also discuss pertinent issues regarding allocation procedures and present important complexity results. Our presentation of theoretical issues is complemented by a discussion of software packages for the simulation of agent-based market places. We also introduce four major application areas for multiagent resource allocation, namely industrial procurement, sharing of satellite resources, manufacturing control, and grid computing.
Keywords: informatika; information science; agentni sistemi; alokacija virov; avtonomni agenti